Standing Against Patriarchal Culture in ElSaadawi's Woman at Point Zero - DEWI, ARIVIANI (2011)
ARIVIANI DEWI. NIM: S. 200 090 021. Standing Against Patriarchal Culture in El Saadawi's Woman at Point Zero. A thesis. Magister of Language Study, School of Graduate Studies, Muhammadiyah University of Surakarta, 2011. The objectives of the research are (1) to reveal the revolt against patriarchal culture, and (2) to get to know the response of the reader toward literary work. The method of the research is descriptive qualitative. The data source derived from books, scientific journals, news, and virtual sources. The present researcher uses note taking to collect the data and uses phenomenological approach on literary critics for data analyzing technique. The uses of radical feminist theory and reader response theory will help for a comprehensible understanding. This study has examined El Saadawi's protest in Woman at Point Zero and its effects in the community. It has discovered that El Saadawi's protest against inequality and oppression in Egyptian society has contributed to social change. The portrait of the oppressed women in highly Islamic patriarchal culture as the result of monolithic interpretation of religious teaching calls the world's attention. She portrays the impact of religion to women's subordination whether in economics, education, social, politics and culture. The finding moves further that women's subordination has led to other oppression which manifest in the violence against women such as verbal violence, rape or marital rape, physical violence and female genital mutilation. The last mentioned is the most polemical issue which last for over decades. This study has further discovered that the issue exposed in the novel that is responded by national and international institution has significant effect in the society. The effect in its native country is manifest in the government policies, reported news and researches whereas the international effect is the eliminating of violence against women. The issue related to gender inequality which comes from monolithic interpretation of religious teaching becomes a favorite theme in the academic community. Many Muslim scholars conduct a research and the finding is because of misreading of the sacred scripture, thus the scholars suggest people to rereading the holy book for a justice community.